THE IMPLEMENTATION OF THE MARRIAGE AGE LIMIT - Dita Nabila Jania Liswan; Syamsul Bahri (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Article 7, Paragraph (1) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage states that